2000
DOI: 10.1159/000027775
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Traumatic Tympanic Membrane Perforations and Pneumatization of the Mastoid

Abstract: We evaluated the possible relationship between tympanic membrane perforations resulting from blast trauma or slap and pneumatization of the mastoid cells. A total of 25 male patients with tympanic membrane perforations resulting from blast injury (n = 7), slap (n = 17), and football hit (n = 1) and 20 healthy male volunteers without any ear problem had temporal bone computed tomographic scans in the axial plane, parallel to the infraorbitomeatal line, with 2 mm slice thickness and 2-mm intervals using bone alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
3
6
1
Order By: Relevance
“…It has also been reported that the average ME volumes in the normal ears, as measured using CT, were 5.6-7.9 mL, which is similar to our results (3-6). …”
Section: Discussionsupporting
confidence: 92%
“…It has also been reported that the average ME volumes in the normal ears, as measured using CT, were 5.6-7.9 mL, which is similar to our results (3-6). …”
Section: Discussionsupporting
confidence: 92%
“…The method of evaluating pneumatization in this study was precise and convenient, and differed from the previous studies. [11][12][13][14][15][16][17][18] The volume of pneumatization including air cells and tympanic cavity was calculated and found to be similar to other studies. [13][14][15][16][17][18] It was found x The authors speculate that this information may be of help to surgeons that there were correlations between the pneumatization and all the measured parameters of the facial nerve.…”
Section: Discussionsupporting
confidence: 77%
“…An estimation of the ME volume change required to generate the measured postural pressure change was calculated by employing Boyle's law of gases: P 1 × V 1 = P 2 × V 2, where P is the pressure and V is the volume. The volume of ME cleft ( V 1) was taken as 8 mL, which may be considered the average normal aerated mastoid size 8–10. The initial, upright pressure ( P 1) was atmospheric pressure (10,000 mmH 2 O) + the tympanometric average upright recording.…”
Section: Methodsmentioning
confidence: 99%